Não somos filhos sem pais: história e teologia do batuque do Rio Grande do Sul - Silveira, Hendrix Alessandro Anzorena (2014)
The goal of this paper is to understand the history and the theology of the Traditions of African Origin structured in the state of Rio Grande do Sul and called Batuque. It seeks to comprehend how Batuque underwent it epistemological destitution; it attributes meanings and purposes to the rituals of this tradition based on a theological reflection founded on an interdisciplinary, Afrocentric and post-colonial epistemology; it grants us knowledge of this tradition from its African origins up to the local restructuring; it helps researchers on the theme as well as professionals in the area of education, especially in the fields of Theology, Sciences of Religion and Religious Education; it also gives tools to those who live out Batuque, the batuqueiros, who, due to historical persecution, had their ancestral knowledge destitute with the epistemicide devised by the colonialism of the white man . This thesis has four chapters. In the first we deal with the African tradition in its relation with its history and culture. In the second we talk of the Africans who were trafficked to Brazil during the slave system, about how the diaspora process took place and the restructuring in Rio Grande do Sul. In the third we detail the systematic persecution of this tradition: the epistemicide. The fourth chapter will discourse about Afrotheology, its methodological presuppositions and attempts at systematization.